Optimizing Job Satisfaction in Mediating Motivation on Lecturer Performance - Khairatun Nazah; Sabaruddin Chaniago; Berupilihen Br Ginting; Martin Martin; Amin Hou (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2021)
Job satisfaction gives hope, especially for a lecturer in improving his welfare. Having good work motivation is expected to be able to increase the quantity and quality of lecturers in carrying out their duties and responsibilities. The main focus of this study is to determine the role of job satisfaction in mediating motivation on performance. This research method uses a Structure Equation Model (SEM) based on Partial Least Square (PLS). In this study, the population and sample were 52 permanent lecturers of the LP3M Superior Polytechnic. Data collection techniques using a questionnaire. The results of data analysis show that motivation directly has a positive and significant effect on job satisfaction, indirectly motivation does not affect performance. Job satisfaction has a positive and significant effect on performance. Indirectly job satisfaction has a role in mediating motivation to performance.